Auricular Pseudocyst: Sonographic Appearance in 17 Patients. Issue 4 (December 2021) - Whittle, Carolina; Castro, Alex; Pereira, Maria Jose; Cabrera, Raul
Abstract : Abstract: Auricular pseudocyst (AP) is a rare benign condition that corresponds to an intracartilaginous collection resulting in a noninflammatory cystic swelling of the ear. The objective is to describe ultrasound and clinical presentation of histologically proven AP. An Institutional Review Board (IRB) approved a 6-year retrospective study. Patients with an auricular pseudocyst were selected. Fifty-nine percent of the cases were referred with clinical suspicion of AP. One hundred percent were men, and in 76% of the cases, AP was located in the scaphoid fossa. The mean age was 35 years (76% from 20 to 50 years). Unilateral lesion was present in 94% of the cases. A single lesion was found in 88% and multiple lesions in 12%. On high-resolution ultrasound increased thickness of the cartilage was observed in all patients with a cystic lesion inside the cartilage. Fifty-nine percent of the cases were totally anechoic. The other presented echoes or septa inside the cystic lesion. In conclusion high-resolution ultrasound allows to study the exact anatomic involvement of the cartilage and the surrounding tissues. The auricular pseudocyst presented a characteristic ultrasound finding permitting an adequate early diagnosis and monitoring treatment. Knowledge of this pathology and the sonographic finding is important for a correct diagnosis.